Perbandingan Pendekatan Pidana Restoratif dan Retributif dalam Penyelesaian Kasus Kejahatan di Indonesia secara Hukum dan Sosial - Sitti Munawwarah; Tumian Lian Daya Purba; Kaharuddin Syah; Irsyad Sudirman; Muhammad Aiman (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the comparison between restorative and retributive criminal justice systems in resolving criminal cases in Indonesia. The background of this study is the growing urgency to implement a more humanistic criminal justice model that not only focuses on punishment or retaliation, but also emphasizes efforts to restore the losses of victims and achieve reconciliation between perpetrators, victims, and the community. This study aims to analyze the fundamental differences between the two approaches, assess their effectiveness in the Indonesian context, and identify challenges in their implementation. A qualitative approach is applied through literature review and policy analysis by examining legal regulations, law enforcement practices, and implementation experiences across various judicial institutions. The findings reveal that the retributive justice system remains dominant, particularly in cases involving serious and violent crimes. However, the restorative justice model has been increasingly introduced in minor offenses and complaint-based cases, especially through mechanisms such as mediation and community involvement. Restorative justice is found to offer greater potential in reducing recidivism rates, increasing victim satisfaction, and promoting long-term social harmony. Despite its advantages, the implementation of restorative justice in Indonesia still faces multiple challenges, including limited regulatory support, lack of public awareness, and resistance within legal institutions due to entrenched punitive mindsets. This study concludes that a balanced integration of restorative and retributive approaches is necessary, depending on the nature and severity of the crime. Strengthening the legal framework, enhancing institutional capacity, and promoting a cultural shift within law enforcement are crucial steps toward establishing restorative justice as a legitimate, humane, and sustainable alternative in Indonesia’s criminal justice system.